Implementation And Development Of Islamic Mutual Funds In Indonesia - Saputra , Muhammad Redo (Utami Publisher, 2024)
This article is motivated by several studies regarding the development and application of sharia mutual funds in Indonesia, as well as looking at the conditions occurring in the world of the Indonesian capital market, which is currently becoming a trend among young economists. This article aims to provide deeper insight into the application and development of sharia mutual funds that have occurred in Indonesia, looking at various existing research and literature sources. The author uses a literature study writing method by reviewing several journals and literature related to the development and application of sharia mutual funds that have occurred in Indonesia. The results of this research will later be used to provide and clarify insight into the implementation and development of sharia mutual funds in Indonesia.